Don't cancel the surgery just yet! A case report of positive preoperative pregnancy test due to a soft tissue sarcoma production of ectopic beta human chorionic gonadotropin. (August 2018) - Blank, Alan Todd; Khalighi, Mazdak; Randall, R Lor; Jones, Kevin B
Soft tissue sarcomas are a rare group of mesenchymal malignancies which can range from low to high grade. These tumors have different clinical, radiographic, and histopathological characteristics. Beta human chorionic gonadotropin is a naturally secreted hormone by placental syncytiotrophoblast cells during pregnancy. On very rare occasions, sarcomas can develop the ability to ectopically produce human chorionic gonadotropin. Very few cases exist in the literature of soft tissue sarcomas expressing this hormone. We report the case of a 55-year-old female who presented with a posterior thigh soft tissue sarcoma who on the day of surgical resection was found to have an unusually elevated serum human chorionic gonadotropin. Positive immunohistochemical staining of the resected mass confirmed the sarcoma as the source of the beta human chorionic gonadotropin.